Characterization of Ax[W6I14] as Key Compounds for Ligand‐Substituted A2[W6I8L6] Clusters. Issue 31 (28th September 2016) - Hummel, Thorsten; Ströbele, Markus; Schmid, Dominic; Enseling, David; Jüstel, Thomas; Meyer, H.‐Jürgen
Abstract : A x [W6 I14 ] compounds with A = Na, K, Rb, or Cs are prepared from W3 I12 and alkali iodides (AI). Crystal structures were solved and refined for Na[W6 I14 ] and A2 [W6 I14 ] compounds with A = K, Rb and Cs on the basis of powder and single‐crystal XRD diffraction. All compounds behave stable in air and can be dissolved in polar organic solvents making them valuable precursors for long‐needed soluble octahedral [W6 I8 I6 ] 2– cluster ions. Excitation and emission spectra of solid Na[W6 I14 ] and Cs2 [W6 I14 ] are reported as reference systems for photophysically active A2 [W6 I8 L6 ] compounds (L = inorganic or organic ligand), which can be developed therefrom, as demonstrated for Na2 [W6 I8 (OCH3 )6 ]· 8(CH3 OH). Abstract : A x [W6 I14 ] compounds with A = Na, K, Rb, or Cs are prepared from W3 I12 and alkali iodides (AI) by means of solid‐state reactions. All compounds can be dissolved in polar organic solvents making them valuable precursors for soluble octahedral [W6 I8 I6 ] 2– cluster ions, as demonstrated for Na2 [W6 I8 (OCH3 )6 ]· 8(CH3 OH). Excitation and emission spectra of solid Na[W6 I14 ] and Cs2 [W6 I14 ] are reported.